-13-2a=-8a+79(54+5a)

Simple and best practice solution for -13-2a=-8a+79(54+5a) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -13-2a=-8a+79(54+5a) equation:



-13-2a=-8a+79(54+5a)
We move all terms to the left:
-13-2a-(-8a+79(54+5a))=0
We add all the numbers together, and all the variables
-2a-(-8a+79(5a+54))-13=0
We calculate terms in parentheses: -(-8a+79(5a+54)), so:
-8a+79(5a+54)
We multiply parentheses
-8a+395a+4266
We add all the numbers together, and all the variables
387a+4266
Back to the equation:
-(387a+4266)
We get rid of parentheses
-2a-387a-4266-13=0
We add all the numbers together, and all the variables
-389a-4279=0
We move all terms containing a to the left, all other terms to the right
-389a=4279
a=4279/-389
a=-11

See similar equations:

| 5+2(-4c+20)=17-c | | 3y+10=2(-5y+5)-2y | | 1/2(h)-12=-5 | | 3x-41=-2(-2x-7)-6x | | -7y+7(1+2y)=-2y-11 | | (1/2)h-12=-5 | | -8-3(44-5y)=-2y+13 | | 6p+4/6=4p-83 | | 20×x=50 | | -2k-25=2(-4k-39)-1 | | -2x-15=10-2x-25 | | 4^2+20x=0 | | 8n=–6+7n | | 5+7x=-128 | | 7(-3y-5)+9=-8y | | 9x=5x+4(2x-13) | | -10a-24(5a+48)=-2a | | -5+24=-8t-15 | | 11=10(3a+31)+1 | | 3^(2x-3)=4^x | | 12=4(4y-18)-9y | | -43(3z-35)-5=-4z | | (3x-1)(2x-9)=90 | | 8(1)+2y=-6 | | 2(2x-6)-8=4(3x-2) | | 9x-18=5x-2 | | 2b-3b=+4b | | s=0.8(24) | | 6912=(18x+6x)*18x | | 3x^2+6x+2=4 | | b=(0.75)90 | | 10.1x-1.6x+44=7 |

Equations solver categories